2017
DOI: 10.1111/dom.12908
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of autoinjected exenatide once‐weekly suspension versus sitagliptin or placebo with metformin in patients with type 2 diabetes: The DURATION‐NEO‐2 randomized clinical study

Abstract: AimsGlucagon‐like peptide‐1 receptor agonists and dipeptidyl peptidase‐4 inhibitors treat type 2 diabetes through incretin‐signaling pathways. This study compared the efficacy and safety of the glucagon‐like peptide‐1 receptor agonist exenatide once‐weekly (Miglyol) suspension for autoinjection (QWS‐AI) with the dipeptidyl peptidase‐4 inhibitor sitagliptin or placebo.Materials and methodsIn this open‐label, multicentre study of patients with type 2 diabetes who had suboptimal glycaemic control on metformin mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…Exenatide QW was available as a vial and syringe (single‐dose tray), or as a single use prefilled pen injector; however, both presentations required patients to mix exenatide‐containing microspheres and aqueous diluent prior to the injection. So as to improve the convenience of use prior to injection, exenatide QW suspension (QWS) was developed for use with an autoinjector device, in which the microspheres are suspended in 0.774 g Miglyol 812, a mixture of medium chain triglycerides (MCTs), in a 2 mg dose of exenatide QWS (Gadde, Vetter, Iqbal, Hardy, & Ohman, ; LaRue & Malloy, ). MCTs are a class of lipids whose fatty acid chains contain from six to 12 carbon atoms (medium chain fatty acids or MCFA; Gadde et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exenatide QW was available as a vial and syringe (single‐dose tray), or as a single use prefilled pen injector; however, both presentations required patients to mix exenatide‐containing microspheres and aqueous diluent prior to the injection. So as to improve the convenience of use prior to injection, exenatide QW suspension (QWS) was developed for use with an autoinjector device, in which the microspheres are suspended in 0.774 g Miglyol 812, a mixture of medium chain triglycerides (MCTs), in a 2 mg dose of exenatide QWS (Gadde, Vetter, Iqbal, Hardy, & Ohman, ; LaRue & Malloy, ). MCTs are a class of lipids whose fatty acid chains contain from six to 12 carbon atoms (medium chain fatty acids or MCFA; Gadde et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…So as to improve the convenience of use prior to injection, exenatide QW suspension (QWS) was developed for use with an autoinjector device, in which the microspheres are suspended in 0.774 g Miglyol 812, a mixture of medium chain triglycerides (MCTs), in a 2 mg dose of exenatide QWS (Gadde, Vetter, Iqbal, Hardy, & Ohman, ; LaRue & Malloy, ). MCTs are a class of lipids whose fatty acid chains contain from six to 12 carbon atoms (medium chain fatty acids or MCFA; Gadde et al, ). The fatty acids in MCTs are caproic acid (C6), caprylic acid (C8), capric acid (C10) and lauric acid (C12).…”
Section: Introductionmentioning
confidence: 99%
“…Among the newer classes of anti‐hyperglycaemic agents approved in the USA is exenatide, the first‐in‐class glucagon‐like peptide 1 (GLP‐1) receptor agonist. Multiple studies have demonstrated the efficacy of exenatide in controlling blood glucose levels and in promoting weight loss, with known side effects of nausea and/or vomiting (N/V) . All currently marketed formulations of exenatide and other GLP‐1 receptor agonists are administered by injection.…”
Section: Introductionmentioning
confidence: 99%
“…
In Gadde et al [1], on page 981, in the section 2.6 Statistical Analysis, second paragraph in second column contained some missing text. The paragraph should have read:

The primary endpoint was assessed using a mixed-effects model repeated measures (MMRM) with change in HbA1c as the dependent variable; treatment, week of visit, treatment-by-week interaction, screening HbA1c stratum and screening HbA1c stratum-by-week interaction as fixed effects; and patient as random effect.

…”
mentioning
confidence: 99%
“…In Gadde et al [1], on page 981, in the section 2.6 Statistical Analysis, second paragraph in second column contained some missing text. The paragraph should have read:…”
mentioning
confidence: 99%